Kobiety w zawodach inżynierskich – dynamika dostępu do studiów i kariery zawodowej - Szymczak , Emilia (Studia Edukacyjne, 2018)
This article describes the history of women in the engineering world, the changing social and economic conditions and women’s rising educational aspirations (it appears that they are interested in the traditional scientific disciplines but they also increasingly with to try typically male – form the point of view of traditional socialization – educational and then professional careers). The article presents the dynamics of the access of women to higher education through the years, including especially scientific and technical fields of study. It also presents the statistical data about the participation of women in the stereotypically male areas of education. This article provides historical examples of women, famousbecause of their spectacular scientific achievements.